8+2(x+6)=-2+2x-2

Simple and best practice solution for 8+2(x+6)=-2+2x-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8+2(x+6)=-2+2x-2 equation:



8+2(x+6)=-2+2x-2
We move all terms to the left:
8+2(x+6)-(-2+2x-2)=0
We add all the numbers together, and all the variables
2(x+6)-(2x-4)+8=0
We multiply parentheses
2x-(2x-4)+12+8=0
We get rid of parentheses
2x-2x+4+12+8=0
We add all the numbers together, and all the variables
24!=0
There is no solution for this equation

See similar equations:

| −4(r+8)=−62 | | -3(4x-6)=2x-3 | | -2=-3x+2x | | 10=2x-6x+5 | | 12=3-2k+3k | | 15-4y=8(7y-9) | | -16=8(4r-9) | | -24=6+4(x-7) | | -7b-5b=-17 | | -9a-5+4a=30 | | -3n+2=-4n+5= | | 400+.07x=750 | | 9+7(1-8c)=-19 | | 9+7(1-8c)=19 | | 150+0.70x=307.50 | | -6(7n-8)=34 | | 6+5y=44 | | 2965+7x=610+155x | | 150+0.07x=307.50 | | x^2-18x+210=0 | | 2x+(2xx1)=132 | | 26-2x=8x+44 | | 15+.10x=18+.08x | | (2-3y)=(5-y) | | -10x-8=-5x+37 | | -9x+5-3x=11 | | -1.75=1/2+w | | 4x+10=5(x+1) | | -3x+49=4(4x-2) | | 32=2(3x-2) | | 6x+26=-22 | | 3(x+5)^2=81 |

Equations solver categories